Solitary Cecal Ulcer: A Case Report - Li, Chun Qiang; He, An-Qi; Liu, Gang (Frontiers in Surgery, 2022)
Background: Solitary cecal ulcer is a rare disease. The etiology is unknown, and there are no pathognomonic symptoms. There are rare reports mimicking carcinoma as seen in this case. Case Presentation: A 64-year-old woman presented with a history of intermittent right lower abdominal pain for 20-year and worsening for 1 year. Colonoscopy revealed an enormous cecal ulcer. The positron emission tomography-computed tomography(PET-CT) showed increased metabolism of the lesion. She underwent a right hemicolectomy. Histopathological examination revealed chronic nonspecific inflammation. A rare diagnosis of solitary cecal ulcer was ultimately made. Conclusion: Solitary cecal ulcer is a rare, idiopathic entity. It mimics inflammatory bowel disease, malignancy, and infection etc. These comprehensive images of this case describe the characteristics of the disease.